Предмет: Алгебра,
автор: D1sa25
(tga+ctga)\ (tga-ctga), если tga = 3\2
Ответы
Автор ответа:
6
tga=3/2(по условию) => ctga = 1 : 3/2 = 2/3
Тогда:
(tga+ctga)/(tga-ctga)=(3/2+2/3)(3/2-2/3) = ((9+4)/6)/((9-4)/6) =
= 13/6 : 5/6 = 13/5
Тогда:
(tga+ctga)/(tga-ctga)=(3/2+2/3)(3/2-2/3) = ((9+4)/6)/((9-4)/6) =
= 13/6 : 5/6 = 13/5
Похожие вопросы
Предмет: Українська мова,
автор: alionazelik
Предмет: Английский язык,
автор: nobioyet
Предмет: Русский язык,
автор: savchenkoivan2019
Предмет: Математика,
автор: Kate693
Предмет: Химия,
автор: Mandarinkfaff